Impact of Risk Asset Management on Financial Performance of Listed Deposit Money Banks in Nigeria - , Amakwe, Rose-Mary Ngozi, Nwankwo Arinze Henry, Ndukwe Orji Dibia, John Uzoma Ihendinihu, Ude Obasi Ogbu (Archives of Current Research International, 2025)
The financial feat of Deposit Money Banks (DMBs) in Nigeria is influential to its economic growth and development. DMBs generally play a vital role in the development of the economy. The major role of a bank is embedded in its intermediation function of transferring funds from surplus units to the deficit units through lending activities. This study investigated the effect of risk asset management on the financial performance of selected listed DMBs in Nigeria. The study applied a descriptive and ex-post facto research design. The sample size was twelve (12) listed deposit money banks selected from a population of all the listed deposit banks within the period of study from 2012-2022. Data for the study were extracted from secondary sources, specifically annual reports and accounts of the selected deposit money banks for the period. Data generated for this study were analysed using the panel Generalised Method of Moments (GMM) of the E-Views 10 statistical package. The results revealed that loans and advances, as well as investment securities, have a significant positive influence on the return on equity of DMBs in Nigeria. The values of m-statistics for both AR (1) and AR (2) of -0.980663 and 0.035556 have proven to be insignificant at 5% level (p-values of 0.3268 and 0.9716 are both > 0.05). Therefore, the null hypothesis that proposes the absence of serial correlation is not rejected, and it is concluded that there is no serial correlation in the series. The probability of the J-statistic of 8.380227 is reported as 0.397237, and this affirms the validity of the model as supporting evidence for the results obtained using the first differences transformation. The study concluded that risk asset management has a significant positive impact on the financial performance in accordance with the A priori expectation of the study. The study therefore recommends that risk assets of deposit money banks should be consistently analysed and classified to reduce the level of non-performing loans, while resources should be channelled in the area of loans and advances and in investment securities as they impact positively on the returns generated by listed deposit money banks in Nigeria.